The Farm Management Survey 1966 to 1969 - Heavey, John F. (Statistical and Social Inquiry Society of Ireland, 1972)
Farm management surveys are now a relatively common feature in developing and developed countries. Their prominence is largely due, no doubt, to increased interest and concern with social and economic equity amongst all sectors of the population. The widespread use and acceptance of soaial and economic planning at national level has accentuated the need for objective and functional information on farm incomes and the farm economy.
Read before the Society, 12 May 1972
Keywords: Farm management survey; Irish agriculture; Productivity in Irish agriculture; 314.15